2015
DOI: 10.3109/23337931.2015.1084883
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of gold-titanates on Gram-positive cariogenic bacteria

Abstract: Objective: Gram-positive cariogenic bacteria are etiological agents in dental caries; therefore, strategies to inhibit these bacteria to reduce the incident of this disease have intensified. In this study, we investigated antibacterial activities of titanates and gold-titanates against Lactobacillus casei (Lc) and Streptococcus mutans (Sm). Materials and methods: Monosodium titanate (MST), nanomonosodium titanate (nMST) and amorphous peroxo-titanate (APT), which are inorganic compounds with high-binding affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This again may reflect on the strength of the Au-PMS interaction. One would expect that NPs/PMS would bind through several metals ions or atoms in the microbial cell [24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This again may reflect on the strength of the Au-PMS interaction. One would expect that NPs/PMS would bind through several metals ions or atoms in the microbial cell [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Such properties make NPs powerful tools for vast and diverse applications (e.g. antimicrobial, diagnosis, imaging, and thereby drug delivery (because NPs provide unprecedented opportunities to molecular process and interrogate cellular clinical application [24] )). NPs have recently emerged as unique anti-microbial agents due to their shape, size and high surface area to volume ratio; NPs are of the same dimensions as proteins, nucleic acid, membrane of receptors, antibodies and other biomolecules [25] .…”
Section: Antimicrobial Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] However, it was observed that as the concentration of silver oxide increased from 0.5 to 2 wt%, the growth inhibition of P. aeruginosa increased from 72% to 85%, while the growth inhibition of S. epidermidis decreased from 89% to 47%. Initially, we measured the antibacterial activity of silicate glasses with increasing percentages of silver oxide (0.5-1-1.5-2 wt%) It is clear from the figure that significant growth inhibition was observed for both strains.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…It is due to the known antibacterial activity of Ag + on both gram-positive and gram-negative bacteria. [25][26][27] However, it was observed that as the concentration of silver oxide increased from 0.5 to 2 wt%, the growth inhibition of P. aeruginosa increased from 72% to 85%, while the growth inhibition of S. epidermidis decreased from 89% to 47%. The different responses can be ascribable to the different cell wall structures of both model bacteria, gram-positive, and gram-negative.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%